Perceiving in depth. Volume 3, Other mechanisms of depth perception - Howard, Ian P. (Oxford : Oxford University Press, 2012)
This volume addresses depth-perception mechanisms other than stereopsis.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Depth perception